Podoba generala Maistra v nemškokoroški propagandni publicistiki - Domej, Teodor (Studia Historica Slovenica, 2025)
The image of General Maister in the German-Carinthian propaganda media of 1918–1920 is consistently negative. The article discusses not only the two-year border dispute between Yugoslavia and Austria after the collapse of AustriaHungary, but also its long prehistory since 1848, when the doctrine of the indivisibility of Carinthia was created. A characteristic of Carinthia in the last period of the Habsburg monarchy is the unbalanced position of the Slovene- and German-speaking population. The main basis of the article are articles in Carinthian German newspapers and in two distinctly propaganda bulletins of the German-Carinthian camp (Kärntner Landsmannschaft, Koroško Korošcem), which discuss General Maister.
Keywords: agitacija; border conflict; campaining; Carinthia; Carinthian plebiscite; Koroška; koroški plebiscit; Maister, Rudolf; mejni konflikt; narodnostni konflikt; national conflikt